The reactivation of silent memories in the work of Patrícia Francisco - Ribeiro, Niura (PORTO ARTE: Revista de Artes Visuais, 2019)
Abstract Revisiting the past of social and cultural processes has been one of the ways contemplated by certain contemporary artistic practices. And for this, research in archives has been fundamental to elaborate a critical-aesthetic reflection. The text addresses the poetry of artist Patrícia Francisco, who seeks to reactivate the silenced memories of the enslaved, through works materialized in photographs, video performances, objects and installations. Thinking about memory and forgetting are important vectors that can contribute to the awareness that atrocities will not happen again. Resumo Revisitar o passado de processos sociais e culturais tem sido um dos caminhos contemplados por determinadas práticas artísticas contemporâneas. E para tal, pesquisas em arquivos têm sido fundamental para elaborar uma reflexão crítico-estética. O texto aborda a poética da artista Patrícia Francisco que procura reativar as memórias silenciadas dos escravizados, por meio de obras materializadas em fotografias, em vídeo performances, objetos e instalações. Pensar sobre a memória e o esquecimento são vetores importantes que podem contribuir para conscientização de que atrocidades não voltarão a acontecer.